2017
DOI: 10.1186/s12887-017-0933-6
|View full text |Cite
|
Sign up to set email alerts
|

Emerging (val)ganciclovir resistance during treatment of congenital CMV infection: a case report and review of the literature

Abstract: BackgroundCongenital cytomegalovirus (cCMV) infection is an important illness that is a common cause of hearing loss in newborn infants and a major cause of disability in children. For that reason, treatment of symptomatic patients with either ganciclovir or its pro-drug valganciclovir is recommended. Treatment duration of 6 months has been shown to be more beneficial than shorter courses; however, there is uncertainty regarding emergence of resistance strains, secondary effects and long term sequelae.Case pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The second child (case 2) reported a modest developmental delay. We agree with other authors (Campanini et al, 2012;Benzi et al, 2012;Choi et al, 2013;Morillo-Gutierrez et al, 2017) that a prolonged therapeutic exposure may be a risk factor for resistance in cCMV patients, and thus viral load surveillance is the key in monitoring early onset of resistance to V-GCV/GCV. Time-scheduled viral load assessments allow prompt identification of resistance, avoiding ineffective therapy and related ADs, even if the current literature mainly indicates that long-term therapy, after the initial period, does not account for ADs while ongoing (Amir et al, 2010;James and Kimberlin, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…The second child (case 2) reported a modest developmental delay. We agree with other authors (Campanini et al, 2012;Benzi et al, 2012;Choi et al, 2013;Morillo-Gutierrez et al, 2017) that a prolonged therapeutic exposure may be a risk factor for resistance in cCMV patients, and thus viral load surveillance is the key in monitoring early onset of resistance to V-GCV/GCV. Time-scheduled viral load assessments allow prompt identification of resistance, avoiding ineffective therapy and related ADs, even if the current literature mainly indicates that long-term therapy, after the initial period, does not account for ADs while ongoing (Amir et al, 2010;James and Kimberlin, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…The benefit of measurement of CMV genome load in treatment for congenital CMV infection has not been well reported. Morillo-Gutierrez et al (15) reported that periodic viral load testing is important to identify emerging resistance strains of CMV during antiviral therapy. In the present case, intravenous ganciclovir therapy appeared to be clinically effective.…”
mentioning
confidence: 99%
“…The compounds 13f and 13k showed virus inhibition in this assay; however, much more concentration is required that may be impractical to attain physiologically. Considering widespread resistance against GCV in clinical strains of HCMV and well-known side effects such as neutropenia, compound 13m exhibited a moderate activity (IC 50 = 19 μM), which could lead to future drug discovery for HCMV. …”
Section: Resultsmentioning
confidence: 99%